Medial Smooth Muscle Cell Proliferation in the Balloon Injured Rabbit Aorta: Effect of a Thiazole Compound with Platelet Inhibitory Activity - Schaub, R G; Simmons, C A (Thrombosis and Haemostasis, 1984)
Twenty-seven adult male New Zealand rabbits (3–4 kgs) were used in this study. Six rabbits received vehicle, 3 groups of 6 each received doses of 4,5-bis(p-methoxyphenyl)-2-(trifluoromethyl)- thiazole, (U-53,059), at 0.3 mg/kg, 3.0 mg/kg and 30.0 mg/kg/day respectively. Drug and vehicle doses were given orally each day starting 3 days before balloon injury and continuing for the entire 2 week time period. Three rabbits were used as nontreated sham controls. In the vehicle and U-53,059 treated groups aortae were denuded of endothelial cells by balloon catheter injury. Two weeks after injury platelet aggregation to collagen was measured and the aortae removed for analysis of surface characteristics by scanning electron microscopy and lesion size by morphometry. All doses of U-53,059 inhibited platelet aggregation. The 3.0 and 30.0 mg/kg groups had the greatest inhibitory effect. All balloon injured aortae had the same morphologic characteristics. All vessels had similar extent and intensity of Evan’s blue staining, similar areas of leukocyte/platelet adhesion, and a myointimal cell cover of transformed smooth muscle cells. The myointimal proliferative response was not inhibited at any of the drug doses studied.
Keywords: Anti-atherogenic; Proliferation; Platelet; Adhesion; Inhibition and leukocyte